Transcriptome Analysis of Turbot (Scophthalmus maximus) Infected With Aeromonas salmonicida Reveals a Direct Effect on Leptin Synthesis as a Neuroendocrine Mediator of Inflammation and Metabolism Regulation - Librán-Pérez, Marta; Pereiro, Patricia; Figueras, Antonio; Novoa, Beatriz (Frontiers in Marine Science, 2022)
Aeromonas salmonicida subsp. salmonicida is the causative agent of furunculosis, a disease affecting numerous fish species worldwide. It is a highly pathogenic bacterium for turbot, whose farming production represents an important economic activity in several European countries and China. To better understand the response of this organism to A. salmonicida, we conducted RNA-Seq analysis of the head kidney from experimentally infected and uninfected turbot juveniles at 24 hours post-infection (hpi). As expected, among the differentially expressed genes (DEGs) between infected and uninfected fish, we observed the modulation of a multitude of immune-related genes but also a high representation of genes linked to metabolism. Interestingly, one of the most upregulated genes was that encoding the hormone leptin. Leptin is a multifunctional hormone/cytokine that has been shown to play roles in the immune system, stress response, food intake, metabolism and energy balance. We used recombinant human leptin to elucidate its role during infection with A. salmonicida in turbot (anorexigenic activity, ability to modulate metabolism and the immune response, and its effect on survival and bacterial load during infection). We found that the intraperitoneal administration of leptin was able to alter the response to the bacteria at the immune level, but especially at the metabolic level, which resulted in a higher survival rate without affecting the bacterial load. Based on this, we hypothesized that leptin could offer great potential as a therapeutic treatment during furunculosis outbreaks by reducing the impact of sepsis. Our results reveal the complex interplay between bacterial activity and the regulation of food intake, metabolism and inflammation.